2017
DOI: 10.1073/pnas.1704294114
|View full text |Cite
|
Sign up to set email alerts
|

Distinct roles for motor neuron autophagy early and late in the SOD1 G93A mouse model of ALS

Abstract: Mutations in autophagy genes can cause familial and sporadic amyotrophic lateral sclerosis (ALS). However, the role of autophagy in ALS pathogenesis is poorly understood, in part due to the lack of cell type-specific manipulations of this pathway in animal models. Using a mouse model of ALS expressing mutant superoxide dismutase 1 (SOD1), we show that motor neurons form large autophagosomes containing ubiquitinated aggregates early in disease progression. To investigate whether this response is protective or d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
155
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(171 citation statements)
references
References 64 publications
14
155
0
2
Order By: Relevance
“…Autophagy is an important cellular homeostatic pathway responsible for the clearance of misfolded or aggregated proteins. The inhibition of autophagy in MN of the SOD1 mice leads to the acceleration of the disease onset , and in contrast, autophagy inhibition in symptomatic animals resulted in the suppression of glial activation and prolonged survival . Its role in ALS might therefore be positive at the earlier stage, however, at later stages the effect could be negative.…”
Section: Discussionmentioning
confidence: 97%
“…Autophagy is an important cellular homeostatic pathway responsible for the clearance of misfolded or aggregated proteins. The inhibition of autophagy in MN of the SOD1 mice leads to the acceleration of the disease onset , and in contrast, autophagy inhibition in symptomatic animals resulted in the suppression of glial activation and prolonged survival . Its role in ALS might therefore be positive at the earlier stage, however, at later stages the effect could be negative.…”
Section: Discussionmentioning
confidence: 97%
“…Interactions between motor neurons and glia contribute to motor neuron loss, but the spatiotemporal ordering of molecular events that drive these processes in intact spinal tissue remains poorly understood. Here, we use spatial transcriptomics to obtain gene expression measurements of mouse spinal cords over the 5 course of disease, as well as of postmortem tissue from ALS patients, to characterize the underlying molecular mechanisms in ALS. We identify novel pathway dynamics, regional differences between microglia and astrocyte populations at early time-points, and discern perturbations in several transcriptional pathways shared between murine models of ALS and human postmortem spinal cords.…”
mentioning
confidence: 99%
“…However, the events that initiate disease pathology, and the mechanisms through which pathology spreads remain poorly understood (1)(2)(3)(4). Mounting evidence indicates that dysfunction in signaling between motor neurons and glia is a key component of the disease (1,5,6). Inherent limitations of widely available gene expression profiling technologies, such as low throughput or lack of spatial 20 resolution have thus far frustrated efforts to understand how such dysfunction participates in the onset and spread of ALS pathology in the spinal cord.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of oxidative stress in neurodegenerative disease began with the initial identification of superoxide dismutase 1 (SOD1) as the first ALS-associated mutation (Rosen et al, 1993). Subsequent studies have identified a diverse array of functional pathways altered in SOD1 mutant mouse models, including SOD-1 mediated autophagy (Rudnick et al, 2017), proteotoxic stress (Bruijn et al, 1998), and neuroinflammation (Chiu et al, 2013), reflecting both the pleiotropic roles played by SOD1 protein as well as different manifestations depending on the cellular context in which SOD1 is dysfunctional. Since that initial discovery, several genes with roles in oxidative stress, proteotoxic stress, and autophagy have been linked to ALS (Taylor et al, 2016).…”
Section: The Als-ox Group Displays Evidence Of Oxidative Stressmentioning
confidence: 99%